Stress and quality of life: the influence of some personal variables - Sadir, Maria Angélica; Bignotto, Márcia Maria; Lipp, Marilda Emmanuel Novaes (Paidéia (Ribeirão Preto), 2010)
Stress is a health problem common both in the professional and personal spheres and has many causes. This study investigated the impact of some personal variables on levels of stress and quality of life in a sample of 106 male and female adults who were attending an outpatient psychology clinic. Mean age average was 38.5 years. Participants were classified according to profession and evaluated through a Quality of Life Inventory and the Lipp Stress Symptom Inventory. Results indicated that 88% of the participants had high stress level and quality of life was compromised, especially in terms of health. A significant association between stress and gender was found, but not between job position and inferred level of stress. There was compatibility between self-diagnosis of stress and clinical diagnosis.